Implementasi Media Pembelajaran Sains dan Teknologi Miniatur Longsor Berbasis IoT di SD Negeri Lulu - Anastasia Kadek Dety Lestari; Regolinda Maneno; Emanuel M.Y. Hanoe; Guido Adolfus Suni (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
North Central Timor Regency has a high level of landslide vulnerability, while students’ understanding of disaster mitigation remains low. This community service program aims to enhance the science and technology literacy of students at SD Negeri Lulu through learning activities using an Internet of Things (IoT)-based landslide miniature as an educational medium. The miniature is designed to simulate landslide processes with IoT sensors that monitor soil moisture, allowing students to directly observe the relationship between environmental conditions and landslide potential. Through this activity, science and technology learning becomes more contextual, interactive, and engaging for elementary school students. The program also supports Sustainable Development Goals (SDGs) 4 (Quality Education), 11 (Sustainable Cities and Communities), and 13 (Climate Action). The integration of technology in science education has proven effective in improving students’ understanding of abstract geophysical and environmental concepts. Through experiments using the IoT-based miniature, students not only gain theoretical knowledge but also understand the practical application of technology in analyzing natural phenomena. This activity is expected to serve as a model for science and technology learning based on disaster mitigation in landslide-prone areas.